Closed-form estimators for the inverse Nakagami distribution - VICTOR NAWA; SARALEES NADARAJAH (Anais da Academia Brasileira de Ciências)
Abstract The inverse Nakagami distribution due to Louzada et al. (2018) does not have closed-form maximum likelihood estimators. Closed-form estimators by adapting the method of moments are proposed in this note. Also proposed is a bias corrected version of the estimators. Large sample properties including asymptotic variances of the proposed estimators are derived. A simulation study and data applications are provided to compare the performances of the maximum likelihood estimators, the proposed estimators and their bias corrected versions.